Decision-making process about prenatal genetic screening: how deeply do moms-to-be want to know from Non-Invasive Prenatal Testing? - Serena Oliveri; Giulia Ongaro; Ilaria Cutica; Giulia Menicucci; Debora Belperio; Francesca Spinella; Gabriella Pravettoni (BMC, 2023)
Abstract Background Prenatal information may be obtained through invasive diagnostic procedures and non-invasive screening procedures. Several psychological factors are involved in the decision to undergo a non-invasive prenatal testing (NIPT) but little is known about the decision-making strategies involved in choosing a specific level of in-depth NIPT, considering the increased availability and complexity of NIPT options. The main aim of this work is to assess the impact of psychological factors (anxiety about pregnancy, perception of risk in pregnancy, intolerance to uncertainty), and COVID-19 pandemic on the type of NIPT chosen, in terms of the number of conditions that are tested. Methods A self-administered survey evaluated the decision-making process about NIPT. The final sample comprised 191 women (Mage = 35.53; SD = 4.79) who underwent a NIPT from one private Italian genetic company. Based on the test date, the sample of women was divided between "NIPT before COVID-19" and "NIPT during COVID-19". Results Almost all of the participants reported being aware of the existence of different types of NIPT and more than half reported having been informed by their gynecologist. Results showed no significant association between the period in which women underwent NIPT (before COVID-19 or during COVID-19) and the preferences for more expanded screening panel. Furthermore, regarding psychological variables, results showed a significant difference between perceived risk for the fetus based on the NIPT type groups, revealing that pregnant women who underwent the more expanded panel had a significantly higher level of perceived risk for the fetus than that reported by pregnant women who underwent the basic one. There was no statistically significant difference between the other psychological variables and NIPT type. Conclusions Our findings indicate the paramount role of gynecologist and other health care providers, such as geneticists and psychologists, is to support decision-making process in NIPT, in order to overcome people's deficits in genetic knowledge, promote awareness about their preferences, and control anxiety related to the unborn child. Decision-support strategies are critical during the onset of prenatal care, according to the advances in prenatal genomics and to parent's needs.